The Ambiguity of Adat Law and National Land Law Implementation in Land Sale and Purchase Agreement - Fathoni, M. Yazid; Wagian, Diangsa; Adha, Hadi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2025)
The purpose of this study is to determine the concept of the validity of land sale and purchase agreements in Indonesia, related to the judge's legal considerations in Court Decision Number 596/K/Pdt 2012. The research method in this study uses the normative research method by case study. The results of this study showed that the concept of the Indonesian Land Sale and Purchase Agreement under Law Number 5 of 1960 and Government Regulation Number 24 of 1997, the transfer of land rights is considered to occur when a PPAT sale and purchase deed is made. However, because the UUPA was formed based on Adat Law, there are principles in practice and court decisions, the transfer of land rights through sale and purchase can be carried out according to customary law/Adat Law by fulfilling the elements of real, clear, and cash. However, the uniqueness of this decision, even though the parties did it in the customary way, the judge's legal consideration in decision Number 596 / K / Pdt 2012 is based on the Civil Code/ Burgerlijk Wetboek.